MORPHOLOGICAL CHARACTERISTICS OF GOBIO LEPIDOLAEMUS KESSLER, 1872 (TELEOSTEI: GOBIONIDAE) IN THE SO'X RIVER BASIN (Scientific journal of the Fergana State University, 2025)
The Sokh River, due to its geographical location, is classified as a mountain river, and its ichthyofaunal species composition differs from that of plain water bodies. Until recently, the ichthyofauna of this river was known to comprise three fish species. During this study, for the first time, a small population of the Turkestan gudgeon (Gobio lepidolaemus), an endemic species of the Syr Darya basin, was recorded in the middle reaches of the Sokh River. Although the Turkestan gudgeon typically inhabits plain water bodies, this research provides evidence of its gradual migration into cold-water mountain rivers. This article discusses the morphological characteristics of the Turkestan gudgeon recorded for the first time in the ichthyofauna of the Sokh River. The speciesʼ morphometric and meristic characteristics were examined using collected specimens and compared with data from populations in other water bodies.The Sokh River is considered a mountain river based on its geographical location and differs from plain water basins in terms of its ichthyofauna species composition. Until now, there was information about the presence of three fish species in this river. During this study, for the first time, a small population of the Turkestan loach (Gobio lepidolaemus), an endemic of the Syr Darya basin, was discovered in the middle flow of the Sokh River. The habitat of the Turkestan loach is primarily associated with plain water basins, and its gradual migration towards cold-water mountain rivers was demonstrated during the research. This article discusses the morphological characteristics of the Turkestan loach, which has been recorded for the first time in the ichthyofauna of the Sokh River. The morphometric and meristic parameters were analyzed based on the collected samples and compared with the parameters of populations from other water basins.